Mortalidade materna no município de Belém, Pará no ano de 2004 - Assunção, Maria José Magalhães de (2005)
Maternal mortality is one of the main health indicators for women in childbearing age, thus reflecting the quality of the health care system and the access the populations has to its services. Even with growing investments aimed to reduce such mortality, the rates continue high, especially in developing countries. The complications of hypertension in pregnancy, of abortion, the hemorrhages and puerperal infection still prevail as causes of maternal deaths and, most of the times, result from inadequate care the woman receives during the puerperal pregnancy cycle. Maternal mortality is still a serious problem to be faced in Brazil. However, very little is known about its real magnitude. In some places, maternal death is disguised in the Death Certificate (DC) with causes that can only be known through investigation. This shows the need to investigate the deaths of women in childbearing age by means of sources other than the DC such as hospital records, prenatal records, necropsy reports, information gathered from family members and from those professionals who assisted the patient. Since maternal death is such an event with a high degree of avoidability, it is necessary to identify its causes and the factors that might be contributing to its occurrence so that the magnitude of maternal death can be known, thus allowing for prevention-oriented strategies to be established. This study aimed to describe the profile of maternal mortality in the city of Belém, Pará State, in 2004. The work is presented as an article and its data sources were the Mortality Information System, the Information System on Live Births, referring to 2004 data, hospital and prenatal records, reports by the Medico-Legal Institute (IML), and interviews with the patients’ family members. The results found show that the Maternal Mortality Ratio in Belém is high and that most of the maternal deaths in 2004 were considered as avoidable by means of adequate care during prenatal, parturition and puerperium.